ANALISIS YURIDIS PENYELESAIAN PELANGGARAN LALU LINTAS YANG DILAKUKAN OLEH MILITER DALAM PERSPEKTIF KRIMINOLOGI - Sandy Arya Prathama; Mau, Hedwig Adianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study aims to analyze the legal resolution of traffic violations committed by military personnel within the framework of criminology, focusing on a case study in the Kogartap I/Jakarta area. Traffic violations involving military personnel raise complex issues related to legal authority, military jurisdiction, and the interaction between civil and military law. The research employs a qualitative approach with a criminological perspective to examine how military personnel are handled in cases of traffic violations, focusing on both the legal procedures and the sociological implications of these violations. The study found that military personnel involved in traffic violations are typically subject to military law, but the legal process often intersects with civilian law, leading to challenges in enforcement and adjudication. This research contributes to the understanding of the intersection between military and civilian legal systems, emphasizing the need for clearer protocols and more effective coordination between civil and military authorities to address such violations. The study also explores the criminological aspects of military involvement in traffic offenses, highlighting factors such as discipline, accountability, and the impact of military culture on behavior in the civilian sphere.